On the quasiuniqueness of solutions of degenerate equations in Hilbert space - Vladimir Schuchman (International Journal of Mathematics and Mathematical Sciences)
In this paper, we study the quasiuniqueness (i.e., f1≐f2 if f1−f2 is flat, the function f(t) being called flat if, for any K>0, t−kf(t)→0 as t→0) for ordinary differential equations in Hilbert space. The case of inequalities is studied, too.